2013
DOI: 10.1136/sextrans-2013-051288
|View full text |Cite
|
Sign up to set email alerts
|

Recent partner violence and sexual and drug-related STI/HIV risk among adolescent and young adult women attending family planning clinics

Abstract: Background/Objectives Adolescent and young adult women are at high risk for both STI/HIV and intimate partner violence (IPV). We evaluate the prevalence of IPV in the past three months and its associations with STI/HIV risk, STI, and related care-seeking over the same time period. Methods Female family planning clinic patients ages 16–29 (n=3,504) participated in a cross-sectional survey in 2011–2012 as a baseline assessment for an intervention study. We examined associations of recent IPV with sexual and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 27 publications
5
59
4
1
Order By: Relevance
“…Research on IPV, reproductive coercion, and reproductive health has illustrated the ways in which partner-perpetrated physical and sexual violence and coercion impact women's ability to negotiate condom use. 7,40,41 In the current analysis, IPV was an important confounder of the relationship between sexual minority status and health, which further illustrates how powerful IPV can be for women's sexual and reproductive health, regardless of the sex of women's sexual partners. However, the impact of abuse on women's health did differ with respect to lifetime history of an STI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research on IPV, reproductive coercion, and reproductive health has illustrated the ways in which partner-perpetrated physical and sexual violence and coercion impact women's ability to negotiate condom use. 7,40,41 In the current analysis, IPV was an important confounder of the relationship between sexual minority status and health, which further illustrates how powerful IPV can be for women's sexual and reproductive health, regardless of the sex of women's sexual partners. However, the impact of abuse on women's health did differ with respect to lifetime history of an STI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Women in violent relationships are also less likely than nonabused women to refuse sex or use condoms during intercourse. [12][13][14] Women's reluctance to use condoms may stem from fear of physical or sexual violence. 12 In addition, the psychological sequelae of partner violence (e.g., depression, suicidal ideation) as well as substance abuse, which is associated with IPV victimization, have been shown to increase sexual risk taking and thus contribute to HIV infection.…”
Section: Hiv and Ipv: Intersecting Public Health Epidemicsmentioning
confidence: 99%
“…15 When the co-occurring substance use involves injection drug use, women may additionally be at risk of HIV through shared needles. Studies have demonstrated that women experiencing partner violence are more likely to inject drugs than women who do not experience partner violence, 14 and women who inject drugs are more likely to engage in sex with partners who inject drugs.…”
Section: Dual Protection Against Sexual and Injection Riskmentioning
confidence: 99%
“…In relation with drugs use, a higher risk of STI/HIV has been described associated to substance use, and attributable to unsafe sexual behaviors [17,18]. Although this association has been clearly established in MSM [35,36], those assisted by the Services had sexual intercourses under the drugs effect less frequently than in other studies [15,18], with data even lower than MSW, and there was no association with the detection of reactive results.…”
Section: Discussionmentioning
confidence: 87%
“…Different factors have been associated to this higher risk, like having suffered previous STI [13,14], or the use of drugs before or during sexual intercourse [15,17,18]. Among MSM the role of serodiscordant relationships in newly acquiring infection is well-recognised [15,19], and persistent unprotected anal intercourse with occasional partners is predictor of seroconversion [20].…”
Section: Introductionmentioning
confidence: 99%